Current Perspectives: Evidence to Date on BTK Inhibitors in the Management of Multiple Sclerosis - Carnero Contentti E; Correale J (Dove Medical Press, 2022)
Edgar Carnero Contentti,1 Jorge Correale2,3 1Neuroimmunology Unit, Department of Neuroscience, Hospital Alemán, Buenos Aires, Argentina; 2Department of Neurology, Fleni, Buenos Aires, Argentina; 3Universidad de Buenos Aires-CONICET, Instituto de Química y Fisicoquimíca Biológicas (IQUIFIB), Buenos Aires, ArgentinaCorrespondence: Edgar Carnero Contentti; Jorge Correale, Email ecarnerocontentti@hospitalaleman.com; jcorreale@fleni.org.arAbstract: Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system leading to demyelination and neurodegeneration. Basic and translational studies have shown that B cells and myeloid cells are critical players for the development and course of the disease. Bruton’s tyrosine kinase (BTK) is essential for B cell receptor-mediated B cell activation and for normal B cell development and maturation. In addition to its role in B cells, BTK is also involved in several functions of myeloid cells. Although significant number of disease-modifying treatments (DMTs) have been approved for clinical use in MS patients, novel targeted therapies should be studied in refractory patients and patients with progressive forms of the disease. On the basis of its role in B cells and myeloid cells, BTK inhibitors can provide attractive therapeutic benefits for MS. In this article, we review the main effects of BTK inhibitors on different cell types involved in the pathogenesis of MS and summarise recent advances in the development of BTK inhibitors as novel therapeutic approaches in different MS clinical trials. Available data regarding the efficacy and safety of these drugs are described.Keywords: multiple sclerosis, tyrosine kinase inhibitors, Bruton’s tyrosine kinase inhibitors, autoimmune diseases, experimental autoimmune encephalomyelitis